Arm Span is an Alternative to Standing Height for Calculation of Body Mass Index (BMI) amongst Older Adults - Arlappa Nimmathota; Aatif Qureshi Ihtesham; Philip Ravikumar Baer; Balakrishna Nagalla; Arbaab Qureshi Mohtashim (International Journal of Nutrition, 2016)
Objectives: Accurate measurement of height is difficult in older adults because of the reduction in height that occurs during the ageing process. Therefore, several western studies have demonstrated the arm span as an alternative anthropometric measurement to height among older adults, as the length of arm span is less affected by aging. The aim of the study was to use arm span as an alternative to standing height for calculation of body mass index (BMI) amongst older adults. Methodology: A community-based cross sectional study was carried out during 2011-12 among 400 (Men: 180; Women: 220) urban geriatric population (age 60-years and over)of the town of Khammam. Weight, height and arm span were measured with standard procedures. Nutritional status of older adults was calculated by body mass index (BMI) classification using both height and arm span. Key Results: The mean (SD) height and arm span among men were 164.5 cm (6.6) and 175.3cm (7.9), respectively, while among women were 149.5cm (5.8) and 158.7cm (8.6). The mean difference between arm span and height was 10.8cm (10.1,11.4)in men and 9.2cm (8.3,10.0) in women (p<0.001). Similarly, significant (p<0.001) differences were observed between the BMIs derived using both height and arm span among both the genders. Conclusion: The conventional height is not a reliable anthropometric measurement for the assessment of nutritional status of older adults, where the BMI-height model over estimated the nutritional status of older adults compared to the BMI- arm span model. Therefore, arm span is the best alternative to height for calculation of body mass index (BMI) in older adults.
Keywords: Body Mass Index